Observations on Interaction between the Indian Whip Spider Phrynichus phipsoni (Amblypygi: Phrynichidae) and Fungoid Frog Hydrophylax bahuvistara (Anura: Ranidae) in a Cave Ecosystem of Goa, India - Borkar, Manoj R.; Sail, Pratiksha; D'Sa, Vinita Q; Lizanne, A.C. Maria (Journal of the Bombay Natural History Society (JBNHS), 2025)
No Abstract.